Characterization of soil aggregation and soil organic matter in European agricultural soils - Lehtinen, Taru, 1981- (2014)
This thesis presents the results of studies of the dynamics of soil aggregates and soil organic matter (SOM), and of studies of the effects of crop residue (CR) incorporation on soil organic carbon (SOC) and greenhouse gas emissions. An improved method for macroaggregate breakdown using low-energy ultrasonication and density fractionation was used to investigate the soil aggregate dynamics and SOM in European agricultural soils. The greatest aggregate breakdown was observed in Andisol and Entisol, followed by Alfisol, Ultisol, and Inceptisol. The stability of macroaggregates was influenced by particle-size distribution and the amounts of exchangeable Mn and Mg. In Iceland and Austria, evidence of diminished aggregate hierarchy was observed. Mn oxides in Iceland and Fe oxides in Austria were positively correlated with macroaggregation, as was fungal biomass. In Iceland, in low SOM concentration sites macroaggregates contributed 40-70% of the organic carbon and nitrogen to bulk soil, whereas in high SOM concentration sites free particulate organic matter contributed up to 70% of the OC and N to bulk soil. In Austria, the slightly different SOM distributions between the sites were most likely caused by differences in soil texture and maybe soil age. Analyses of published data on the effect of CR incorporation on SOC and greenhouse gas emissions in Europe indicate a 7% increase in SOC. In contrast, CO2 and N2O emissions were six and twelve times higher, respectively. The processes linking CR incorporation to soil aggregate and SOM dynamics needs to be clarified in future studies. Lífrænt kolefni í jarðvegi og samkornun jarðvegs eru mikilvæg fyrir gæði hans. Þessi ritgerð fjallar um gagnkvæma virkni lífræns efnis og samkorna í jarðvegi á ræktarlandi í Evrópu, en beitt var nýrri aðferð við sundrun stórra samkorna til að auðvelda rannsóknirnar. Ritgerðin fjallar einnig um áhrif blöndunar lífrænna leifa af ræktarlandi í jarðveg á lífrænt kolefni í jarðvegi og losun gróðurhúsalofttegunda. Samkornin ...